Efficiency of Islamic Banks in African Arabic Countries An Application of Data Envelopment Analysis’ - bessadet, karima (My University, 2012)
We have tried through the article to address how to identify and demonstrate the efficiency of banks in general and Islamic in particular and we have been selected to the Arab and African countries, depending on the data related to this activity in these countries to highlight the degree of efficiency of each bank in each country and try to identify the most shortcomings related to Activity and try to remedy them.
Keywords: Research Subject Categories::SOCIAL SCIENCES